Parable of the sower - Butler, Octavia E. 1947-2006 (Grand Central Publishing, 2019)
"In 2025 California, an eighteen-year-old African American woman, suffering from a hereditary trait that causes her to feel others' pain as well as her own, flees northward from her small community and its desperate savages."
Keywords: americké romány; vědecko-fantastické romány; American fiction; science fiction novels